A mononuclear nonheme iron(iii)-peroxo complex binding redox-inactive metal ions - Lee, Yong-Min; Bang, Suhee; Kim, Yun Mi; Cho, Jaeheung; Hong, Seungwoo; Nomura, Takashi; Ogura, Takashi; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Sarangi, Rikimukta; Fukuzumi, Shunichi; Nam, Wonwoo (Chemical Science, 2013)
Redox-inactive metal ions that function as Lewis acids play pivotal roles in modulating reactivities of oxygen-containing metal complexes in a variety of biological and biomimetic reactions, including dioxygen activation/formation and functionalization of organic substrates. Mononuclear nonheme iron(iii)-peroxo species are invoked as active oxygen intermediates in the catalytic cycles of dioxygen activation by nonheme iron enzymes and their biomimetic compounds. Here, we report mononuclear nonheme iron(iii)-peroxo complexes binding redox-inactive metal ions, [(TMC)Fe(O)] -M (M = Sc and Y ; TMC = 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane), which are characterized spectroscopically as a 'side-on' iron(iii)-peroxo complex binding a redox-inactive metal ion, (TMC)Fe-(μ, η:η-O)-M (2-M). While an iron(iii)-peroxo complex, [(TMC)Fe(O)], does not react with electron donors (e.g., ferrocene), one-electron reduction of the iron(iii)-peroxo complexes binding redox-inactive metal ions occurs readily upon addition of electron donors, resulting in the generation of an iron(iv)-oxo complex, [(TMC)Fe(O)] (4), via heterolytic O-O bond cleavage of the peroxide ligand. The rates of the conversion of 2-M to 4 are found to depend on the Lewis acidity of the redox-inactive metal ions and the oxidation potential of the electron donors. We have also determined the fundamental electron-transfer properties of 2-M, such as the reduction potential and the reorganization energy in electron-transfer reaction. Based on the results presented herein, we have proposed a mechanism for the reactions of 2-M and electron donors; the reduction of 2-M to the reduced species, (TMC)Fe-(O)-M (2′-M), is the rate-determining step, followed by heterolytic O-O bond cleavage of the reduced species to form 4. The present results provide a biomimetic example demonstrating that redox-inactive metal ions bound to an iron(iii)-peroxo intermediate play a significant role in activating the peroxide O-O bond to form a high-valent iron(iv)-oxo species. © 2013 The Royal Society of Chemistry.

Catalytic phenol hydroxylation with dioxygen: Extension of the tyrosinase mechanism beyond the protein matrix - Hoffmann, Alexander; Citek, Cooper; Binder, Stephan; Goos, Arne; Rübhausen, Michael; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Wasinger, Erik W.; Stack, T. Daniel P.; Herres-Pawlis, Sonja (Angewandte Chemie International Edition, 2013)
A new catalyst (see structure) hydroxylates phenols with O via a stable side-on peroxide complex, which is similar to the active site of tyrosinase in terms of the ligand environment and its spectroscopic properties. The catalytic oxidation of phenols to quinones proceeds at room temperature in the presence of NEt and even non-native substrates can be oxidized catalytically. The reaction mechanism is analogous to that of the enzyme-catalyzed reaction. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Characterization of porphyrin-Co(III)-'nitrene radical' species relevant in catalytic nitrene transfer reactions - Goswami, Monalisa; Lyaskovskyy, Volodymyr; Domingos, Sergio R.; Buma, Wybren Jan; Woutersen, Sander; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Lu, Hongjian; Cui, Xin; Zhang, X. Peter; Reijerse, Edward J.; DeBeer, Serena; et al. (Journal of the American Chemical Society, 2015)
To fully characterize the CoIII-'nitrene radical' species that are proposed as intermediates in nitrene transfer reactions mediated by cobalt(II) porphyrins, different combinations of cobalt(II) complexes of porphyrins and nitrene transfer reagents were combined, and the generated species were studied using EPR, UV-vis, IR, VCD, UHR-ESI-MS, and XANES/XAFS measurements. Reactions of cobalt(II) porphyrins 1P1 (P1 = meso-tetraphenylporphyrin (TPP)) and 1P2 (P2 = 3,5-DitBu-ChenPhyrin) with organic azides 2Ns (NsN3), 2Ts (TsN3), and 2Troc (TrocN3) led to the formation of mono-nitrene species 3P1Ns, 3P2Ts, and 3P2Troc, respectively, which are best described as [CoIII(por)(NR″•-)] nitrene radicals (imidyl radicals) resulting from single electron transfer from the cobalt(II) porphyrin to the 'nitrene' moiety (Ns: R″ = -SO2-p-C6H5NO2; Ts: R″ = -SO2C6H6; Troc: R″ = -C(O)OCH2CCl3). Remarkably, the reaction of 1P1 with N-nosyl iminoiodane (PhI=NNs) 4Ns led to the formation of a bis-nitrene species 5P1Ns. This species is best described as a triple-radical complex [(por•-)CoIII(NR″•-)2] containing three ligand-centered unpaired electrons: two nitrene radicals (NR″•-) and one oxidized porphyrin radical (por•-). Thus, the formation of the second nitrene radical involves another intramolecular one-electron transfer to the "nitrene" moiety, but now from the porphyrin ring instead of the metal center. Interestingly, this bis-nitrene species is observed only on reacting 4Ns with 1P1. Reaction of the more bulky 1P2 with 4Ns results again in formation of mainly mono-nitrene species 3P2Ns according to EPR and ESI-MS spectroscopic studies. The mono- and bis-nitrene species were initially expected to be five- and six-coordinate species, respectively, but XANES data revealed that both mono- and bis-nitrene species are six-coordinate Oh species. The nature of the sixth ligand bound to cobalt(III) in the mono-nitrene case remains elusive, but some plausible candidates are NH3, NH2-, NsNH-, and OH-; NsNH- being the most plausible. Conversion of mono-nitrene species 3P1Ns into bis-nitrene species 5P1Ns upon reaction with 4Ns was demonstrated. Solutions containing 3P1Ns and 5P1Ns proved to be still active in catalytic aziridination of styrene, consistent with their proposed key involvement in nitrene transfer reactions mediated by cobalt(II) porphyrins.

Dramatically accelerated selective oxygen-atom transfer by a nonheme iron(IV)-oxo complex: Tuning of the first and second coordination spheres - Widger, Leland R.; Davies, Casey G.; Yang, Tzuhsiung; Siegler, Maxime A.; Tröppner, Oliver; Jameson, Guy N.L.; Ivanovic-Burmazovic, Ivana; Goldberg, David P. (Journal of the American Chemical Society, 2014)
The new ligand N3PySR and its Fe complex [Fe(N3PySR)](BF) (1) are described. Reaction of 1 with PhIO at -40 C gives metastable [Fe (O)(N3PySR)] (2), containing a sulfide ligand and a single amide H-bond donor in proximity to the terminal oxo group. Direct evidence for H-bonding is seen in a structural analogue, [Fe (Cl)(N3PySR)](BF) (3). Complex 2 exhibits rapid O-atom transfer (OAT) toward external sulfide substrates, but no intramolecular OAT. However, direct S-oxygenation does occur in the reaction of 1 with mCPBA, yielding sulfoxide-ligated [Fe (N3PyS(O)R)](BF) (4). Catalytic OAT with 1 was also observed. © 2014 American Chemical Society.

Encapsulated cobalt-porphyrin as a catalyst for size-selective radical-type cyclopropanation reactions - Otte, Matthias; Kuijpers, Petrus F.; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Reek, Joost N.H.; de Bruin, Bas (Chemistry - A European Journal, 2014)
A cobalt-porphyrin catalyst encapsulated in a cubic ML cage allows cyclopropanation reactions in aqueous media. The caged-catalyst shows enhanced activities in acetone/water as compared to pure acetone. Interestingly, the ML encapsulated catalyst reveals size-selectivity. Smaller substrates more easily penetrate through the pores of the "molecular ship-in-a-bottle catalysts" and are hence converted faster than bigger substrates. In addition, N-tosylhydrazone sodium salts are easy to handle reagents for cyclopropanation reactions under these conditions. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Encapsulation of metalloporphyrins in a self-assembled cubic M 8L6 cage: A new molecular flask for cobalt-porphyrin- catalysed radical-type reactions - Otte, Matthias; Kuijpers, Petrus F.; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Reek, Joost N.H.; de Bruin, Bas (Chemistry - A European Journal, 2013)
The synthesis of a new, cubic ML cage is described. This new assembly was characterised by using NMR spectroscopy, DOSY, TGA, MS, and molecular modelling techniques. Interestingly, the enlarged cavity size of this new supramolecular assembly allows the selective encapsulation of tetra(4-pyridyl)metalloporphyrins (M(TPyP), M=Zn, Co). The obtained encapsulated cobalt-porphyrin embedded in the cubic zinc-porphyrin assembly is the first example of a catalytically active encapsulated transition-metal complex in a cubic ML cage. The substrate accessibility of this system was demonstrated through radical-trapping experiments, and its catalytic activity was demonstrated in two different radical-type transformations. The reactivity of the encapsulated Co(TPyP) complex is significantly increased compared to free Co(TPyP) and other cobalt-porphyrin complexes. The reactions catalysed by this system are the first examples of cobalt-porphyrin-catalysed radical-type transformations involving diazo compounds which occur inside a supramolecular cage. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Gold(I) catalysis at extreme concentrations inside self-assembled nanospheres - Gramage-Doria, Rafael; Hessels, Joeri; Leenders, Stefan H.A.M; Tröppner, Oliver; Dürr, Maximilian; Ivanovic-Burmazovic, Ivana; Reek, Joost N.H. (Angewandte Chemie International Edition, 2014)
Homogeneous transition-metal catalysis is a crucial technology for the sustainable preparation of valuable chemicals. The catalyst concentration is usually kept as low as possible, typically at mm or mm levels, and the effect of high catalyst concentration is hardly exploited because of solubility issues and the inherent unfavorable catalyst/substrate ratio. Herein, a self-assembly strategy is reported which leads to local catalyst concentrations ranging from 0.05m to 1.1m, inside well-defined nanospheres, whilst the overall catalyst concentration in solution remains at the conventional mm levels. We disclose that only at this high concentration, the gold(I) chloride is reactive and shows high selectivity in intramolecular C-O and C-C bond-forming cyclization reactions.
Keywords: Gold; Homogeneous catalysis; Metal-metal interactions; Nanostructures; Supramolecular chemistry

Inside Back Cover: Redox-Active Tetraruthenium Macrocycles Built from 1,4-Divinylphenylene-Bridged Diruthenium Complexes (Chem. Eur. J. 28/2016) - Scheerer, Stefan; Linseis, Michael; Wuttke, Evelyn; Weickert, Sabrina; Drescher, Malte; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Irmler, Andreas; Pauly, Fabian; Winter, Rainer F (Chemistry - A European Journal, 2016)
Keywords: (spectro)electrochemistry; density functional calculations; electrochromism; metallamacrocycle; paramagnetism

Reactions of Superoxide with Iron Porphyrins in the Bulk and the Near-Surface Region of Ionic Liquids - Dees, Anne; Jux, Norbert; Tröppner, Oliver; Dürr, Katharina L.; Lippert, Rainer; Schmid, Martin; Kuestner, Bernd; Schluecker, Sebastian; Steinrück, Hans-Peter; Gottfried, J. Michael; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2015)
The redox reaction of superoxide (KO2) with highly charged iron porphyrins (Fe(P4+), Fe(P8+), and Fe(P8-)) has been investigated in the ionic liquids (IL) [EMIM] [Tf2N] (1-ethyl-3-methylimidazolium bis (trifluoromethylsulfonyl)imide) and [EMIM] [B(CN)(4)] (1-ethyl-3-methylimidazolium tetracyanoborate) by using time-resolved UV/vis stopped-flow, electrochemistry, cryospray mass spectrometry, EPR, and XPS measurements. Stable KO2 solutions in [EMIM] [Tf2N] can be prepared up to a IS mM concentration and are characterized by a signal in EPR spectrum at g = 2.0039 and by the 1215 cm(-1) stretching vibration in the resonance Raman spectrum While the negatively charged iron porphyrin Fe(P8-) does not react with superoxide in IL, Fe(P4+) and Fe(P8+) do react in a two-step process (first a reduction of the Fe(III) to the Fe(II) form, followed by the binding of superoxide to Fe(II)). In the reaction with KO2, Fe(P4+) and Fe(P8+) show similar rate constants (e.g., in the case of Fe(P4+): k(1) = 18.6 +/- 0.5 M-1 s(-1) for the first reaction step, and k(2) = 2.8 +/- 0.1 M-1 s(-1) for the second reaction step). Notably, these rate constants are four to five orders of magnitude lower in [EMIM] [Tf2N] than in conventional solvents such as DMSO. The influence of the ionic liquid is also apparent during electrochemical experiments, where the redox potentials for the corresponding Fe(III)/Fe(II) couples are much more negative in [EMIM] [Tf2N] than in DMSO. This modified redox and kinetic behavior of the positively charged iron porphyrins results from their interactions with the anions of the ionic liquid, while the nucleophilicity of the superoxide is reduced by its interactions with the cations of the ionic liquid. A negligible vapor pressure of [EMIM][B(CN)(4)] and a sufficient enrichment of Fe(P8+) in a close proximity to the surface enabled XPS measurements as a case study for monitoring direct changes in the electronic structure of the metal centers during redox processes in solution and at liquid/solid interfaces.

Redox-Active Tetraruthenium Macrocycles Built from 1,4-Divinylphenylene-Bridged Diruthenium Complexes. - Scheerer, Stefan; Linseis, Michael; Wuttke, Evelyn; Weickert, Sabrina; Drescher, Malte; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Irmler, Andreas; Pauly, Fabian; Winter, Rainer F (Chemistry - A European Journal, 2016)
Metallamacrocylic tetraruthenium complexes were generated by treatment of 1,4-divinylphenylene-bridged diruthenium complexes with functionalized 1,3-benzene dicarboxylic acids and characterized by HR ESI-MS and multinuclear NMR spectroscopy. Every divinylphenylene diruthenium subunit is oxidized in two consecutive one-electron steps with half-wave potential splittings in the range of 250 to 330 mV. Additional, smaller redox-splittings between the +/2+ and 0/+ and the 3+/4+ and 2+/3+ redox processes, corresponding to the first and the second oxidations of every divinylphenylene diruthenium entity, are due to electrostatic effects. The lack of electronic coupling through bond or through space is explained by the nodal properties of the relevant molecular orbitals and the lateral side-by-side arrangement of the divinylphenylene linkers. The polyelectrochromic behavior of the divinylphenylene diruthenium precursors is retained and even amplified in these metallamacrocyclic structures. EPR studies down to T=4 K indicate that the dications 1-H(2+) and 1-OBu(2+) are paramagnetic. The dications and the tetracation of macrocycle 3-H display intense (dications) or weak (3-H(4+) ) EPR signals. Quantum chemical calculations indicate that the four most stable conformers of the macrocycles are largely devoid of strain. Bond parameters, energies as well as charge and spin density distributions of model macrocycle 5-H(Me) were calculated for the different charge and spin states.

Reverse Spin-Crossover and High-Pressure Kinetics of the Heme Iron Center Relevant for the Operation of Heme Proteins under Deep-Sea Conditions - Tröppner, Oliver; Lippert, Rainer; Shubina, Tatyana; Zahl, Achim; Jux, Norbert; Ivanovic-Burmazovic, Ivana (Angewandte Chemie International Edition, 2014)
By design of a heme model complex with a binding pocket of appropriate size and flexibility, and by elucidating its kinetics and thermodynamics under elevated pressures, some of the pressure effects are demonstrated relevant for operation of heme-proteins under deep-sea conditions. Opposite from classical paradigms of the spin-crossover and reaction kinetics, a pressure increase can cause deceleration of the small-molecule binding to the vacant coordination site of the heme-center in a confined space and stabilize a high-spin state of its Fe center. This reverse high-pressure behavior can be achieved only if the volume changes related to the conformational transformation of the cavity can offset the volume changes caused by the substrate binding. It is speculated that based on these criteria nature could make a selection of structures of heme pockets that assist in reducing metabolic activity and enzymatic side reactions under extreme pressure conditions.
Keywords: confined space; heme proteins; high pressure; small-molecule binding; spin crossover

Solution behavior of iron(iii) and iron(ii) porphyrins in DMSO and reaction with superoxide. Effect of neighboring positive charge on thermodynamics, kinetics and nature of iron-(su)peroxo product - Dürr, Katharina L.; Tröppner, Oliver; Olah, J.; Li, Jing; Zahl, Achim; Drewello, Thomas; Jux, Norbert; Harvey, Jeremy N.; Ivanovic-Burmazovic, Ivana (Dalton Transactions, 2012)

Stepwise coordination of PtII-180°and PdII- 90°metal fragments to the purine nucleobase 9-methylhypoxanthine affords a closed octadecanuclear Pt6Pd12 cluster - Albertí, Francisca M.; Zielinski, Witold; Cerda, Marta Morell; Sanz Miguel, Pablo J.; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Lippert, Bernhard (Chemistry - A European Journal, 2013)
Crossing the line: A pH-induced "crossover" in 3D shapes of supramolecular constructs derived from trans(NH)Pt , [Pd(en)], and the purine model nucleobase 9-methylhypoxanthine (see figure) is reported in which [Pd(en)(H O)] and [Pd(en)(OH)] are the decisive players (en=ethylenediamine). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Stereospecific carbene polymerization with oxygenated Rh(diene) species - Walters, Annemarie J.C.; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Tejel, Cristina; del Rio, M. Pilar; Reek, Joost N.H.; De Bruin, Bas (Angewandte Chemie International Edition, 2012)
Breath-taking activation: Stereoregular carbene polymerization proceeds via cationic [(allyl)Rh -polymeryl] species. These are most efficiently generated by oxygenation of the [(diene)Rh ] precatalysts, which involves an unusual rearrangement of 2-rhodaoxetane intermediates. This discovery gives detailed insight in the reaction mechanism. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Tetraalkylphosphonium decavanadates: Synthesis, structures, and solution properties - Mal, Sib Sankar; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Burger, Peter (European Journal of Inorganic Chemistry, 2013)
A novel intercluster compound, [(n-CH) P][HVO] (IL01-V), constructed from the tetrabutylphosphonium cation and decavanadate, has been synthesized and unequivocally characterized by elemental analysis, FTIR spectroscopy, mass spectrometry, X-ray crystallography, and solution H, C, PH, and V NMR spectroscopy. Compound IL01-V was formed by ionic interaction between the phosphonium cation and the decavanadate anion. Cryospray high-resolution mass spectrometry revealed the [HV O] cluster remains intact in solution. Three further phosphonium polyoxovanadates were synthesized and characterized by the same techniques as used for IL01-V. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Thermodynamics and high-pressure kinetics of a fast carbon dioxide fixation reaction by a (2,6-pyridinedicarboxamidato-hydroxo)nickel(II) complex - Tröppner, Oliver; Huang, D.; Holm, R.H.; Ivanovic-Burmazovic, Ivana (Dalton Transactions, 2014)